# Given the point (2,3) and the function f(x) = (-m+1)x + 3, find what is m if the point lies to the graph of the function.

*print*Print*list*Cite

### 2 Answers

We are given that (2,3) lies on the graph of the function f(x) = (-m+1)x + 3.

y = (-m+1)x + 3.

To determine m, substitute x and y from the point (2, 3)

3 = (-m+1)*2 + 3

=> 3 = -2m + 2 + 3

=> -2m + 2 = 0

=> 2m = 2

=> m = 1

**The required value of m = 1**

Since the point (2,3) is located on the graph of f(x), therefore, it must verify the given expression of f(x).

f(2) = 3

We'll replace x by 2 in the expresison of function:

f(2)=(-m+1)*2 + 3

Replacing x by 2, the function take the value of 3.

(-m+1)*2 + 3 = 3

We'll subtract 3 both sides;

(-m+1)*2 = 0

We'll divide by 2:

(-m+1) = 0

We'll isolate m to the left side:

-m = -1

m = 1

**Therefore, for the point (2,3) to be located on the graph of f(x), m takes the value of 1.**